Osservazione e studui sul permafrost in trentino: il Progetto Permanet - SEPPI R.; DALL’AMICO M.; RIGON R.; ZAMPEDRI G.; ZUMIANI M.; CARTON, ALBERTO (2011)
This paper presents the studies on permafrost in Trentino and the key results of the PermaNET project (Permafrost Long-term Monitoring Network). A rock glacier inventory, a statistical model and a permafrost distribution map have been completed, and numerous monitoring activities were initiated. Among these, ground surface temperature measurements are in progress and measurements of the surface displacement of two active rock glacier were continued. Two sites were also equipped to measure the underground temperature and the external climatic parameters, in order to evaluate the permafrost thermal condition in relation to climate change. The cooperation to the project has significantly improved the knowledge of this important feature of the Alpine environment of Trentino.